Studi Tafsir Tematik Lajnah Pentashihan Mushaf Al-Qur′an: Ikhtiar dalam Pengembangan Leadership Skill Generasi Muda - Firmansyah, Reza; Fitriani, Fitriani (Medpro, 2024)
The younger generation is a potential generation, a buffer, and a driver of the relay for the development of human civilization. If a nation is able to foster and succeed in developing its potential optimally so that the mainstream of its cultural pattern is positive, so that the relay of development of human civilization blessed by Allah will still be maintained. However, if the younger generation is left alone and ignored, without any guidance and guidance then of course destruction will approach a nation. Therefore, exploring verses related to the development of leadership skills from the Al-Qur'an perspective needs to be done in order to create a competent young generation based on the Qur'an. Leadership skills have an important role in an organization, in providing evaluation, guidance, and influence on their subordinates in order to be able to achieve common goals effectively and efficiently. This paper focuses on the development of leadership skills from the perspective of the Qur'an which is presented through thematic interpretation, as one of the interpretation models that are expected to be able to answer new problems that occur today. This paper uses a qualitative method with a library research approach and thematic interpretation (Maudhu'i). The results and discussion of this paper include: Leadership skills, views of the Qur'an about the younger generation and their character, and efforts to develop leadership skills in the younger generation according to the Qur'an. This paper concludes that QS An-Nisa (4) verse 9, QS Ali Imran (3) verse 104, QS Al-Anfal (8) verse 60, and QS As-Saff (61) verse 4 as a sign to develop leadership skills of today's young generation. Some of the steps that need to be prepared are by: Preparing cadre drivers/guides, being selective in cadre, considering the character and potential of each cadre, as well as gradual and continuous.